Pengelolaan Sumber Belajar Digital Berbasis E-Library - Mei, Reski; Nasaruddin; Ardiansyah Saputra; Nasrullah (Business Finence Analyst Co.,, 2025)
This study aims to explore the management of digital library-based learning resources (E-Library) at SDIT Wahdah Islamiyah 01 Makassar as a response to the needs of modern technology-based learning, especially during the COVID-19 pandemic. The approach used is qualitative with case study and phenomenology methods, and data collection techniques through observation, in-depth interviews, and documentation. The results show that the E-Zaid Library has made a significant contribution in improving access to digital teaching materials, strengthening students' literacy culture, and encouraging the transformation of a more flexible and adaptive learning process. The system is integrated with the school's academic system and provides various features such as user accounts, activity reporting, and a diverse collection of digital books. With the support of technology, digital libraries are an effective means to meet the needs of information and learning resources efficiently and sustainably. E-Zaid Library is not only a solution in times of crisis, but also an innovative model in digital-based school library management that is relevant in the era of digital transformation of education.